Analisis Persebaran Kawasan Perumahan Tidak Bersusun Oleh Pengembang Di Kecamatan Ngemplak Kabupaten Sleman - Sumarjono, Eko; , Drs. H. M. Musiyam, M.T.P; , Agus Anggoro Sigit, S.Si, M.Sc (2015)
The small-scale residential neighborhood is a local government policy of Sleman district in order to utilize land efficiently, one example is a not-storey residential area by the developer. The purpose of this study were (1) Knowing distribution of residential area that not-storey by the developers in Ngemplak, (2) to analyze the dominant region factors that affect not-storey residential area by developers in Ngemplak. The method used is a visual interpretation of Quickbird imagery to extract the data of physical parameters such as the density of buildings, size of the building, the type of roads, wide roads, the layout of the building of settlements, and socio-economic parameters obtained from secondary data map of the Ngemplak infrastructure, in research this is reinforced by a field survey to obtain data. Distribution of not-storey residential areas by the developers not be determined from the results of the integration between the physical parameters of socio-economic parameters through Scoring methods. Analysis is performed by analyzing the dominant region factors that affect distribution of not-storey residential areas by the developers, these factors are the distance to the city, the distance factor to education facilities, the distance factor to the economy, volcanic hazard. Results of the study are (1) a map of the distribution of not storey residential areas by developers in Ngemplak, where the Wedomartani village is the most widely for not-storey residential areas with extensive residential area measuring 104 hectares. As for the Sindumartani village there is no storey residential area. (2) the dominant factor that determines distribution not-storey residential area by the developer in Ngemplak is Volcano Disaster Risk factors indicated by the lack of the residential areas in the Sindumartani village which is the highest area of the impact of volcanic disaster.